Classification of hadith fi’li in sahih Al-Bukhari based on contextual understanding on the Pillars of Islam - Jamal, Ikmal Hafiz; Junaidi, Juliyana; Khassim, Noor Azma Mohammad; Samarah, Sajedah H A; Khalaf, Najm Abdul Rahman; Malek, Akhdiat Abd; Salam, Rosalina Abdul; Norzulaili Mohd Ghazali; Robiatul Adawiyah Mohd @ Amat; Norhasnira Ibrahim; Syed Najihuddin Syed Hassan; Hishomudin Ahmad (American Scientific Publishers, 2024)
Indexed by SCOPUS